Avtentična razlaga zakona - Zagorc, Saša (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2012)
Author argues that authentic interpretation of law, a legal act inherited from the socialist times, contravenes the very nature of liberal-democratic model of government. It allows the legislature to subsequently interpret the law with ex tunc legal effects. While the interpretation of law by the legislature is undisputed, binding force thereof undermines the core principle of separation of powers, denies a rule of law on the matters of legal certainty and it may also infringe human rights. A move from the subject of interpretation to the method thereof completely reverses the paradigm and leaves the legislator with new clothes on. In Slovenia, the use of authentic interpretation of law worryingly rose in the last term of the parliament. Surprisingly, the Constitutional Court has not been able yet to conclude that the legal act is unconstitutional in its core and purpose, despite the fact that all individual cases of authentic interpretation of law were annuled if brought before the court.
Keywords: parlamenti; parlamentarna demokracija; statute; zakoni; razlaga; interpretacija